The demographics effect on staff absenteeism: A case study on International College of Yayasan Melaka (ICYM) / Anis Zuraida Mohd Zin - Mohd Zin, Anis Zuraida (Bachelor of Science (Hons.) Statistics, 2015)
This study was conducted to examine how certain demographic variables such as gender, staff salary and staff performance affect staff absenteeism and also to identify the association of some variables (staff performance, staff salary, gender). The secondary data from International College of Yayasan Melaka was used in this study. About 185 staff involve in this study. By using Statistical Package of social Science Version 20.0, SPSS20.0 this study found that factor gender not gives significant difference in gender. There is significant difference mean staff absenteeism among difference level of salary (high salary or low salary). Both of this, findings is using independent sample t-test. Analysis of variance (ANOVA) is applied in this research in order to test significant mean different between more than two group and it discover that there is no significant difference mean staff absenteeism among staff performance (excellent, good, satisfactory). By applying Pearson’s Chi-Square test for association, this study revealed that there is no significant association between gender and staff salary, also between staff performance and staff salary. In contrast, there are significant association between gender and staff performance